A Strategy for the Preparation of Thioantimonates Based on the Concept of Weak Acids and Corresponding Strong Bases. Issue 51 (21st October 2014) - Anderer, Carolin; Delwa de Alarcón, Natalie; Näther, Christian; Bensch, Wolfgang
Abstract By following a new synthetic approach, which is based on the in situ formation of a basic medium by the reaction between the strong base Sb(V)S43− and the weak acid H2O, it was possible to prepare three layered thioantimonate(III) compounds of composition [TM(2, 2′‐bipyridine)3][Sb6S10] (TM=Ni, Fe) and [Ni(4, 4′‐dimethyl‐2, 2′‐bipyridine)3][Sb6S10] under hydrothermal conditions featuring two different thioantimonate(III) network topologies. The antimony source, Na3SbS4 ⋅ 9 H2O, undergoes several decomposition reactions and produces the SbIIIS3 species, which condenses to generate the layered anion. The application of transition‐metal complexes avoids crystallization of dense phases. The reactions are very fast compared to conventional hydrothermal/solvothermal syntheses and are much less sensitive to changes of the reaction parameters.